The Preparedness of the Radiologic Technology Program of Davao Doctors College for PACUCOA Accreditation: Basis for an Accreditation Development Plan - Villano, Maria Leah del Fierro (JPAIR Multidisciplinary Research, 2008)
This study aimed to assess the preparedness of the Radiologic Technology Program at Davao Doctors College for PACUCOA accreditation. The independent variables were social position and executive leadership, while the dependent variable was the program’s readiness across nine areas: Purposes and Objectives, Faculty, Instruction, Library, Laboratories, Physical Plant and Facilities, Student Personnel Services, Social Orientation and Community Involvement, and Organization and Administration. Using a descriptive-correlational research design, the study found no significant difference in student and faculty ratings for seven areas—Purposes and Objectives, Instruction, Library, Laboratories, Physical Plant and Facilities, Student Personnel Services, and Social Orientation and Community Involvement—all rated as very good. However, significant differences emerged in Faculty and Organization and Administration ratings; students rated these areas higher than faculty did, though both groups still assessed them as very good. Executive leadership was rated very good by both groups, but social position received differing evaluations: very good from students and good from faculty. A moderate statistical relationship was observed between preparedness for accreditation and social position/executive leadership. The implementation of quality assurance measures at Davao Doctors College strengthened the program’s readiness for accreditation based on PACUCOA criteria. Students showed greater appreciation for provisions in Faculty and Organization and Administration areas. The program’s preparedness is further bolstered by its local and international consortia mechanisms, alumni support, and confidence in executive leadership. These factors affirm successful implementation of quality assurance practices as evidenced by high board examination passing rates among graduates
Keywords: Accreditation; Radiologic Technology